2017
DOI: 10.1177/0142331216683774
|View full text |Cite
|
Sign up to set email alerts
|

Robust control of static Var compensator-based power oscillation dampers using polynomial control in power systems

Abstract: A static Var compensator (SVC) installed in a power transmission network can be effectively exploited to enhance the damping of low frequency electromechanical oscillations. The application of robust control theory offers more reliable and robust damping controller to achieve desired damping level considering variations in the operating conditions of power system. This paper presents a new approach to design a robust proportional-integral (PI) controller for stabilizing power system oscillations. The variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In recent years, despite the fact that different methods presented to eliminate these problems, none has fully addressed them. Various types of balanced structured ERN transformers (Huang et al, 2006; Mazin and Xu, 2009), flexible alternating current transmission system-based static equipment such as Static VAR Compensator (SVC), thyristor-switched capacitor (TSC) and thyristor-controlled reactor (TCR) (Baseri et al, 2011; Hasanvand and Zamani, 2018; Jianzong et al, 2009), Static Synchronous Compensator (STATCOM) (Sadeghi and Fazel, 2010), passive and active filters (Dash and Ray, 2009; Kwon et al, 2014), hybrid active filters (Tan et al, 2004a) are among the most important solutions. However, due to the weaknesses of primary controllers in confronting all power quality (PQ) issues, the need for a comprehensive compensator was always a concern of experts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, despite the fact that different methods presented to eliminate these problems, none has fully addressed them. Various types of balanced structured ERN transformers (Huang et al, 2006; Mazin and Xu, 2009), flexible alternating current transmission system-based static equipment such as Static VAR Compensator (SVC), thyristor-switched capacitor (TSC) and thyristor-controlled reactor (TCR) (Baseri et al, 2011; Hasanvand and Zamani, 2018; Jianzong et al, 2009), Static Synchronous Compensator (STATCOM) (Sadeghi and Fazel, 2010), passive and active filters (Dash and Ray, 2009; Kwon et al, 2014), hybrid active filters (Tan et al, 2004a) are among the most important solutions. However, due to the weaknesses of primary controllers in confronting all power quality (PQ) issues, the need for a comprehensive compensator was always a concern of experts.…”
Section: Introductionmentioning
confidence: 99%
“…12 To reduce oscillations and improve the damping of power systems, various FACTS devices, including the unified power flow controller (UPFC), thyristor controlled series capacitor (TCSC), static synchronous series compensator (SSSC), static var compensator (SVC), and thyristor controlled phase shifter (TCPS), have been proposed. [13][14][15][16] The basic analysis of the incorporation of SVC to improve power system stability is described in Hasanvand and Zamani, 17 and the analysis of the application of SVC to increase LFO damping is also included. It has been demonstrated that the SVC improves the system's ability to damp both local and interarea oscillation modes.…”
mentioning
confidence: 99%